URGENSI ANALISIS CONTEN DALAM PERENCANAAN DAN PENGEMBANGAN PEMBELAJARAN INOVATIV - Achmad Fanani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
Abstract : The purpose of this article is to describe the urgency of content analysis in an innovative learning planning process? teachers tend to plan learning without going through a good and correct analysis process by paying attention to the rules and principles of learning planning, data collection techniques using literacy study techniques and FGD (Focus Group Discussion. Literacy analysis is carried out on the theory of Dick & Carey and Kamp.teknik) learning planning models. The data analysis was carried out in a descriptive analytic manner. The chart of content analysis was one of the stages of the GCT analysis model being developed. The results of the content analysis were used as the basis for the development of teaching materials, Education Participant Activity Sheets (LKPD), and the need for learning resources and media. Content analysis can provide important and complete information on learning materials to support the planning process and the development of learning tools.